The Influence of Competency, Work Experience, Work Environment, and Work Discipline on Employee Performance at Farm Tresno - Hanafi, Farhan; Putu Widhia Rahayu, Ni (Lafadz Jaya Publisher, 2024)
Broiler chicken farming is very vulnerable to environmental changes and price fluctuations, which can sometimes cause disruption. The broiler chicken business does not offer maximum profits if you only consider cultivation alone. The broiler chicken agribusiness system allows farmers to utilize existing human resource management. The aim of this research is to determine the influence of Tresno Farm employees' abilities, professional experience, work environment and work discipline on employee performance. Sampling in this research used a saturated sampling technique, namely a sampling technique when all members of the population were sampled. The sample for this research consisted of 32 Tresno farm employees. This research uses primary data and uses a hypothesis testing method using multiple regression analysis. The research results show that the variables of ability, work experience, work environment and work discipline have a partial or simultaneous effect on the performance of Tresno Farm employees.